2020
DOI: 10.1136/bmjopen-2020-038449
|View full text |Cite
|
Sign up to set email alerts
|

Standard echocardiography versus handheld echocardiography for the detection of subclinical rheumatic heart disease: a systematic review and meta-analysis of diagnostic accuracy

Abstract: ObjectiveTo summarise the accuracy of handheld echocardiography (HAND) which, if shown to be sufficiently similar to that of standard echocardiography (STAND), could usher in a new age of rheumatic heart disease (RHD) screening in endemic areas.DesignSystematic review and meta-analysis.Data sourcesPubMed, Scopus, EBSCOHost and ISI Web of Science were initially searched on 27 September 2017 and again on 3 March 2020 for studies published from 2012 onwards.Eligibility criteriaStudies assessing the accuracy of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In further reviews, the search and exclusion criteria used led to a very specific field of interest and limited retrieval of relevant literature. Telford et al 20 explored articles comparing standard echocardiography machines with handheld equipment, finding high levels of accuracy for handheld ultrasound in detecting definite rheumatic heart disease, though poor accuracy for detection of borderline disease. That review included metropolitan and rural areas, with more focus on proof of concept for handheld devices, rather than the potential benefit of portable devices in low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…In further reviews, the search and exclusion criteria used led to a very specific field of interest and limited retrieval of relevant literature. Telford et al 20 explored articles comparing standard echocardiography machines with handheld equipment, finding high levels of accuracy for handheld ultrasound in detecting definite rheumatic heart disease, though poor accuracy for detection of borderline disease. That review included metropolitan and rural areas, with more focus on proof of concept for handheld devices, rather than the potential benefit of portable devices in low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…conducted a meta-analysis that showed that the HHE had good accuracy for the detection of definite RHD, modest accuracy for the detection of any RHD, and poor accuracy for the detection of borderline RHD. The pooled sensitivity and specificity of HHE for the detection of latent RHD were 81.56 and 89.75%, respectively 48 . However, the HHE was found to overestimate MV morphological abnormalities.…”
Section: Findings and Discussionmentioning
confidence: 98%
“…Other previous studies with nonspecialist professionals had demonstrated the capacity for adequate imaging acquisition and significant-although variable-correlation between screening echocardiography performed by nonspecialists and conventional echocardiography performed by specialists for diagnosing RHD [12,15,30]. This screening strategy is recognized as valid despite exhibiting higher sensitivity than specificity [34][35][36]. Early detection through echocardiographic screening allows for regular clinical monitoring and the implementation of secondary prophylaxis involving the use of G benzathine penicillin to prevent the progression of cardiovascular damage and eventual clinical deterioration [37].…”
Section: Discussionmentioning
confidence: 99%